Perbandingan Efektivitas Podcast dan Musik dalam Pengetahuan Quarter-Life Crisis pada Mahasiswa Universitas Airlangga Surabaya - Nasytha Tristie Wardhani; Sri Widati (Universitas Airlangga, 2023)
Background: Quarter-life crisis is a phase of transition from adolescence to adulthood that occurs starting from the age of 20. In this transitional period, people are considered to be adults and be able to live independently with their own life choices, but emotionally and financially unstable. Health promotion is one of the prevention methods that can be used, one of the example is audio media. Podcasts and music as the medium of health promotion for the quarter-life crisis and the target were the students of Universitas Airlangga Surabaya Objectives: To compare the effectiveness of podcasts and music as health promotion media in providing knowledge about quarter-life crisis. Methods: This study used a quasi-experimental methods and the target were students of Universitas Airlangga batch 2016-2020 with a total sample of 200 respondents. The sample was taken using Lemeshow by Stanley Lemeshow (1997). This study used paired-samples t test and independent sample t test measure. Results: The result of this study showed that there was a difference in knowledge between podcast group and music group. The results of the effectiveness of the media showed that podcast is more effective than music in increasing knowledge. Conclusions: Podcast and music can be a stimulus in increasing knowledge, but podcast is more effective than music in providing knowledge about quarter-life crisis.